Code-Mixing in Digital Communication Among EFL Students in Eastern Indonesia - Ibrahim, Ibrahim; Astini, Fitri Fatika; Saputra, Dian; Hakim, Lukman (Universitas Pendidikan Mandalika, 2025)
In today’s digitally connected world, code-mixing is a key feature of multilingual communication, particularly among English as a Foreign Language (EFL) students in informal online interactions. While digital multilingualism has gained scholarly attention, little is known about how students in peripheral regions such as Eastern Indonesia engage in code-mixing in their daily digital practices. This study investigates how EFL students at Universitas Muhammadiyah Sorong use code-mixing on WhatsApp, Instagram, and Facebook. Employing a qualitative descriptive approach, data were collected through social media observation, screenshot analysis, and semi-structured interviews with purposively selected students from the 3rd, 5th, and 7th semesters. Findings reveal frequent integration of Indonesian, English, and local languages in captions, comments, text messages, and status updates. Code-mixing serves functional and stylistic purposes, such as expressing emotions, narrating experiences, and shaping modern identities, with English use linked to prestige and global trends. Rather than random, it is context-dependent, influenced by audience, topic, and platform. The study highlights code-mixing as a strategic communicative resource and offers implications for pedagogy, digital literacy policy, and future research.